Design and manufacturing of an array of micro IPMC hair-like sensors - Akle, Barbar J. (2016)
Ionic Polymer Metal Composites (IPMCs) are known to be compliant, reliable and able to produce a large current when deformed under a wide range of frequencies. In a previous study, our group demonstrated that cylindrical IPMC hair-like transducers can be used as mechano-electrical sensors. In this paper we characterize the sensing performance of the IPMC hair-like sensor and present methodologies on how to increase its sensitivity while reducing its size. Furthermore an array of 4 hair-cell sensors is built and characterized for tactile sensing texture detection.